Duck-Rabbits in Social Analysis: A Tale of Two Cultures. (February 2013) - Elman, Colin
This article differentiates between three approaches to methodological diversity: monism, pluralism, and eclecticism. It suggests that in advancing a set-theoretic understanding of qualitative research, A Tale of Two Cultures makes an unusually strong argument for robust pluralism. The article anticipates three types of critiques that are likely to be made of the book: Monists will argue that pluralism is an illusion; quantitative researchers will suggest that Goertz and Mahoney inaccurately describe quantitative methods; and qualitative researchers will express doubts as to whether their tradition can be best understood using set theory. The article mainly focuses on the third of these responses, and suggests that even if A Tale of Two Cultures is not always convincing as a descriptive account of current practices, it holds considerable promise as a prescriptive agenda.